A phase I trial of pembrolizumab with hypofractionated radiotherapy in patients with metastatic solid tumours. Issue 10 (13th November 2018) - Maity, Amit; Mick, Rosemarie; Huang, Alexander; George, Sangeeth; Farwell, Michael; Lukens, John; Berman, Abigail; Mitchell, Tara; Bauml, Josh; Schuchter, Lynn; O'Hara, Mark; Lin, Lilie; et al.
Abstract Background We conducted a phase I trial evaluating pembrolizumab+hypofractionated radiotherapy (HFRT) for patients with metastatic cancers. Methods There were two strata (12 patients each): (i) NSCLC/melanoma progressing on prior anti-PD-1 therapy, (ii) other cancer types; anti-PD-1-naive. Patients received 6 cycles of pembrolizumab, starting 1 week before HFRT. Patients had ≥2 lesions; only one was irradiated (8 Gy × 3 for first half; 17 Gy × 1 for second half in each stratum) and the other(s) followed for response. Results Of the 24 patients, 20 (83%) had treatment-related adverse events (AEs) (all grade 1 or 2). There were eight grade 3 AEs, none treatment related. There were no dose-limiting toxicities or grade 4/5 AEs. Stratum 1: two patients (of 12) with progression on prior PD-1 blockade experienced prolonged responses (9.2 and 28.1 months). Stratum 2: one patient experienced a complete response and two had prolonged stable disease (7.4 and 7.0 months). Immune profiling demonstrated that anti-PD-1 therapy and radiation induced a consistent increase in the proliferation marker Ki67 in PD-1-expressing CD8 T cells. Conclusions HFRT was well tolerated with pembrolizumab, and in some patients with metastatic NSCLC or melanoma, it reinvigorated a systemic response despite previous progression on anti-PD-1 therapy. Clinical Trial Registration: NCT02303990 (www.clinicaltrials.gov ).